Tingkat Kepuasan Pasien Universal Coverage Terhadap Pelayanan Kesehatan di Puskesmas Tuminting Manado - Gaghana, Veicy F.; Siagian, Iyone E.T.; Palandeng, Henry M.F.; Monintja, Tyrsa (UNIVERSITAS SAM RATULANGI, 2014)
Patient satisfaction for health care is a level of someone’s feeling after comparing the result of the service they get with their expectation.. Patient satisfaction provides information whether success or not of health care is. Universal Coverage is a free health care program for Manado citizens. Tuminting community health center is a health center that has most listed people in Universal Coverage Program. The purpose of this research is to determine the level of pa-tients satisfaction for health care in Tuminting community health center judges from reliability, responsiveness, as-surance, empathy, tangible and patient overall satisfaction. This is a descriptive research. Samples are collected using purposive sampling technique with sample size as much as 106 Universal Coverage patient who came to Tuminting community health center for medical treatment from October to November 2013. The results shows that 50,9% pa-tients are satisfied with reliability, 54,7% patients are satisfied with responsiveness, 77,4% patients are satisfied with assurance, 55,7% patients are satisfied with empathy, And 66% patients are satisfied with tangible. The overall Uni-versal Coverage patient satisfaction rate for health care is 51,9%. Based on this result, it can be concluded that the health care given by Tuminting community health center to Universal Coverage patient goes along with the order that satisfies patient the most is asssurance, tangibles, empathy, responsiveness, and reliability.Keywords: Satisfaction, health care, Universal Coverage